Computation of surface displacements, tilt and gravity variations due to ocean tide loading - Benavent, M.; Arnoso, J.; Montesinos, F.G. (Física de la Tierra, 2005)
This paper deals with the computation of surface displacements, tilt and gravity variations at the Earth's surface produced by ocean tide loading, through two different methods. The first method consists of the convolution between the ocean tide distribution and the corresponding Green's functions, following the procedure of Farrell (1972). To avoid the Gibbs effect associated to the truncation of the infinite harmonic series, various asymptotic expressions of the load Love numbers are given. Besides, successive improvements of the Farrell's method are also revised. The second method is based on the preliminary development of the ocean tides in spherical harmonics. Thereby, expressions for displacements, gravity and tilt variations in terms of the load Love numbers and the spectral amplitudes of the load are obtained.